2021
DOI: 10.3389/fphys.2021.763195
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Interactions Between Flaviviruses and Mosquito Vectors

Abstract: Mosquito-borne flaviviruses, such as dengue (DENV), Zika (ZIKV), yellow fever (YFV), West Nile (WNV), and Japanese encephalitis (JEV) viruses, threaten a large part of the human populations. In absence of therapeutics and effective vaccines against each flaviviruses, targeting viral metabolic requirements in mosquitoes may hold the key to new intervention strategies. Development of metabolomics in the last decade opened a new field of research: mosquito metabolomics. It is now clear that flaviviruses rely on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 166 publications
(206 reference statements)
0
14
0
Order By: Relevance
“…Further studies have shown that unlike flaviviruses, which actively increase cholesterol biosynthesis, alphaviruses seem to lead to a decrease in cholesterol biosynthesis: suggesting key differences in their requirement for cholesterol [ 31 , 32 , 33 ]. Alphaviruses also utilise host cell membranes, namely plasma membranes, in order to form replication complexes, unlike flaviviruses which are known to utilise ER membranes [ 31 , 34 ]. The lipid composition of ER membranes compared to plasma membranes is fundamentally different, and therefore, the effect of Wolbachia on the availability of cholesterol at each of these membranes is also likely to be different [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown that unlike flaviviruses, which actively increase cholesterol biosynthesis, alphaviruses seem to lead to a decrease in cholesterol biosynthesis: suggesting key differences in their requirement for cholesterol [ 31 , 32 , 33 ]. Alphaviruses also utilise host cell membranes, namely plasma membranes, in order to form replication complexes, unlike flaviviruses which are known to utilise ER membranes [ 31 , 34 ]. The lipid composition of ER membranes compared to plasma membranes is fundamentally different, and therefore, the effect of Wolbachia on the availability of cholesterol at each of these membranes is also likely to be different [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent research has shed light on the critical role of nutrition in determining the outcome of infection in mosquitoes. In particular, lipid metabolism plays a crucial role in the replication and dissemination of arboviruses within the mosquito's body [50][51][52][53][54][55], while amino acids are involved in the mosquito's interaction with the microbiome [45,56]. Given that the mosquito's nutritional status is strongly influences by its microbiome, and that the nutritional status of the mosquito can influence arbovirus infection, it is not surprising that we observe significant variation in the rates of ZIKV infection when mosquitoes are reared in different bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the GLs that were most significantly dysregulated in Cali-MIB+DENV samples were DAGs, TAGs, PC, PE, and PG. These lipids are intricately related; DAG can be converted to PC or PE as membrane components, or the production of TAGs for energy storage [ 60 , 61 ]. Interestingly, TAGs are primarily stored within the cytoplasm in lipid droplets, which are surrounded by a monolayer of amphipathic phospholipids, mainly of PC and PE [ 61 ].…”
Section: Discussionmentioning
confidence: 99%